STUDYING THE ROLE OF HEMOSTASIS SYSTEM GENE POLYMORPHISM IN THE MECHANISMS OF ROSACEA DEVELOPMENT - Agzamkhodjaeva S.S; Azizov B.S; Ayupova Sh.T; Khegay T.R; Dyo K.G (Scholar Express Journals, 2023)
The polymorphism of the genes of the hemostasis system was studied. The study identified genes that are presumably involved in the occurrence and development of rosacea, as well as affecting the severity of the disease. Unfavorable variants of the genes of the hemostasis system, in particular the platelet link: ITGB3: 1565 T>C rs5918, PAI-1: –675 5G>4G rs1799889. The identified loci provide specificity of inflammatory mechanisms in rosacea, and identify potential pathways for therapeutic intervention
Keywords: rosacea; SNP; blood coagulation genes